2004
DOI: 10.1111/j.1365-2850.2004.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and nurse accounts of violent incidents in a Medium Secure Unit

Abstract: Most studies examining violence in a forensic setting have adopted a statistical approach to associate relevant predictors and the likelihood of violence. Views of patients and nurses have been a relatively neglected research area. This study explored patients' and nurses' accounts of violent incidents, considering similarities and differences in their narratives. Permission was obtained from the local National Health Service Research Ethics Board and the Research Ethics Committee of University of East London.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 33 publications
6
74
1
Order By: Relevance
“…seclusion, restraint) rather than engaging and collaborating with patients. This finding is consistent with other research focused on the professional tensions that exist while balancing care and custody in forensic hospitals (Hinsby & Baker, 2004; Mason, 2002; Meehan, McIntosh, & Bergen, 2006). For example, findings of a qualitative study by Hinsby and Baker (2004) suggested that forensic mental health providers tend to give greater weight to maintaining safety and security, as opposed to being caring, as they carry out their clinical duties.…”
Section: Discussionsupporting
confidence: 92%
“…seclusion, restraint) rather than engaging and collaborating with patients. This finding is consistent with other research focused on the professional tensions that exist while balancing care and custody in forensic hospitals (Hinsby & Baker, 2004; Mason, 2002; Meehan, McIntosh, & Bergen, 2006). For example, findings of a qualitative study by Hinsby and Baker (2004) suggested that forensic mental health providers tend to give greater weight to maintaining safety and security, as opposed to being caring, as they carry out their clinical duties.…”
Section: Discussionsupporting
confidence: 92%
“…Communication and engagement between staff and patients have been highlighted as influencing factors in the management of disturbed behaviour (Duxbury & Whittington, 2005;Hinsby & Baker, 2004;Mistral et al, 2002;Whittington & Richter, 2005). The style of communication in engaging the patient is a major influencing factor which cannot be underestimated.…”
Section: The Scip Approachmentioning
confidence: 99%
“…Previous research in this field focuses on different aspects of forensic psychiatric care such as threat, violence, destructive behaviour, protection, aggression, attitudes, practice, and relationships. Men's identity and physical appearance are overlooked despite being important factors in a nursing environment (Daffern, Mayer, & Martin, 2004;Hinsby & Baker, 2004;Rask, 2002;Urheim & Vandenbos, 2006). Threats and violence in forensic psychiatric care are common among male patients.…”
mentioning
confidence: 97%
“…Aggressive behaviour and violent situations are caused by a small number of patients and often are related to existing rules at the unit. These aggressive behaviors are targeted at caregivers and not the patients (Daffern, Mayer & Martin, 2004;Hinsby & Baker, 2004;Urheim & Vandenbos, 2006).…”
mentioning
confidence: 99%